Pemanfaatan Media Pembelajaran Jam Sudut dalam Pembelajaran Matematika di SD - Novi Mayasari; Junarti Junarti; Dian Ratna Puspananda; Ahmad Kholiqul Amin (IKIP PGRI Bojonegoro, 2019)
ABSTRACTBased on the results of observations and interviews with classroom teachers, data were taken into account that students' interest in learning was still low and student learning outcomes were still below the KKM average. Therefore, the PKM lecturer team took the initiative to conduct community service activities by utilizing the angular hour learning media with discussion methods. Corner clock media is a learning medium made from a clock model made of plywood for students, where the clock consists of two circles with one of them larger than the other. The goal to be achieved from this PKM is to help students learn mathematics in a fun way so as to create high interest and better learning achievement. The method of implementation of this PKM program is a method of training directly to fourth grade students of elementary schools in Sukosewu State Elementary School district. Bojonegoro. The results of this PKM activity are the higher learning interest in students which can be seen from the enthusiasm of students and the increasing student achievement results. The conclusion of this PKM activity is that it can increase learning interest and sukosewu elementary school students' learning achievement results in terms of the use of corner hours (jadut) and students are easier to do math problems, especially on mathematics subjects on the subject of angle measurement.Keywords: corner clock learning media, mathematics.Â ABSTRAKBerdasarkan hasil observasi dan wawancara dengan guru kelas diperoh data bahwasanya minat belajar siswa masih rendah dan hasil belajar siswa masih dibawah rata-rata KKM. Oleh karena itu kami tim PKM dosen berinisiatif melakukan kegiatan pengabdian kepada masyarakat Â dengan memanfaatkan media pembelajaran jam sudut dengan metode diskusi. Media jam sudut adalah media pembelajaran yang terbuat dari model jam yang terbuat dari triplek kepada siswa, dimana jam tersebut terdiri dari dua buah Â lingkaran dengan besar salah satunya lebih besar dari lingkaran yang lainnya. Tujuan yang ingin dicapai dari PKM ini adalah membantu siswa belajar matematika dengan cara yang menyenangkan sehingga tercipta minat yang tinggi dan hasil prestasi belajar yang lebih baik. Metode pelaksanaan pada program PKM ini yaitu metode pelatihan secara langsung kepada siswa kelas IV Sekolah Dasar di SD Negeri Sukosewu kab. Bojonegoro. Hasil dari kegiatan PKM ini adalah minat belajar sisiwa semakin tinggi yang dapat dilihat dari antusias siswa dan hasil prestasi belajar siswa yang meningkat. Kesimpulan dari kegiatan PKM ini adalah dapat meningkatkan minat belajar dan hasil prestasi belajar siswa SD negeri sukosewu dalam hal pemanfaatan jam sudut (jadut) dan siswa lebih mudah dalam mengerjakan soal matematika terutama pada mata pelajaran matematika pada pokok bahasan pengukuran sudut.Kata Kunci: Media pembelajaran jam sudut, matematika.